The LCB2 gene of Saccharomyces and the related LCB1 gene encode subunits of serine palmitoyltransferase, the initial enzyme in sphingolipid synthesis. - Nagiec, M M (1994)
The first and committed step in synthesis of the ceramide moiety of sphingolipids is catalyzed by serine palmitoyltransferase (EC 2.3.1.50), which condenses palmitoyl-CoA and serine to form 3-ketosphinganine. This step is thought to be tightly regulated to control the synthesis of sphingolipids, but data supporting this hypothesis are lacking mainly because the enzyme has resisted purification and consequent characterization. Rather than attempting to purify the enzyme from normal cells, we have taken a different tack and opted to try and overproduce the enzyme to facilitate its purification. Here we demonstrate that overproduction in Saccharomyces cerevisiae requires expression of LCB1, a previously isolated yeast gene, and LCB2, the isolation and characterization of which we describe. Several lines of evidence argue that both genes encode subunits of the enzyme; however, biochemical evidence will be needed to substantiate this hypothesis. Although overproduction was modest, 2- to 4-fold, it should now be possible to devise improved overproduction vectors for yeast or other host organisms.